Adaptation of Autumn‐Sown Faba Bean Germplasm to Southeastern Washington. (1st January 2016) - Landry, Erik J.; Coyne, Clarice J.; McGee, Rebecca J.; Hu, Jinguo
Abstract : Information regarding the suitability of autumn‐sown faba bean ( Vicia faba L.) in southeastern Washington is lacking. Therefore, a variety trial testing the effects of two sowing dates was conducted for two seasons (2011–2012 and 2012–2013) at three locations: Central Ferry Research Farm (CF), Pomeroy, WA; Spillman Agronomy Farm (SF), Pullman, WA; Whitlow Farm (WF), Pullman, WA, with 20 northern European breeding lines, or cultivars, and U.S. Department of Agriculture‐Agricultural Research Service National Plant Germplasm System (USDA‐ARS NPGS) sourced germplasm accessions with predetermined winter‐hardiness. Winter‐hardiness and yield varied depending on location, timing of sowing, and genotype effects. Survival was greatest at CF where the extreme low air temperature was –6°C, yet multiple entries tolerated an extreme low of –14°C in Pullman. In both years, the second sowing at the CF location improved survival, whereas the first sowing was only beneficial at the Pullman locations when seedlings were established before the first hard frost. Providing a longer establishment and cold acclimation period was expected to optimize hardiness and yield potential. However, achieving two to three nodes before the first hard frost was difficult at dryland managed SF and WF locations where soil moisture was limiting. Across entries and site‐years, the mean survival was 65% with a yield of 2800 kg ha −1 . To realize the potential of autumn‐sown faba bean in southeastern Washington, genotypes with earlier maturity than the northern European materials tested herein will be needed.